2021
DOI: 10.1021/acs.macromol.0c02598
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Based Aerogels with Tunable Properties: The Highly Efficient BF3-Catalyzed Preparation and Look inside Their Structure

Abstract: This work presents a solution to one of the most fundamentally and practically important challenges in the production of silica-based aerogels, time consumption and expensiveness of these processes, with the main focus on the sol−gel process. We suggested a highly efficient BF 3 -catalyzed method for the production of aerogels, which allows one to shorten the stage of the formation of a (wet) gel to 5 min, the stage of gel aging to 0, while the stage of gel workup is not required; the duration of these stages,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 119 publications
0
8
0
Order By: Relevance
“…[76][77][78] Though some previously reported inorganic silica aerogels showed higher optical transparency compared to the fabricated PI aerogels, in this work, the fabricated PI aerogels presented significantly higher mechanical flexibility and thermal stability. [79][80][81][82]…”
Section: Journal Of Materials Chemistry Cmentioning
confidence: 99%
“…[76][77][78] Though some previously reported inorganic silica aerogels showed higher optical transparency compared to the fabricated PI aerogels, in this work, the fabricated PI aerogels presented significantly higher mechanical flexibility and thermal stability. [79][80][81][82]…”
Section: Journal Of Materials Chemistry Cmentioning
confidence: 99%
“…Detailed structural NMR studies of complex A in a MeCN and chloroform solutions, in which it is well soluble and stable, show the complete identity of its structure with respect to the crystalline state. 1 H, 13 C, 19 F and 11 B NMR spectra show typical chemical shift values for similar types of structures (see the Supporting Information).…”
Section: Resultsmentioning
confidence: 96%
“…54,55 Compound 8 can be used as a binder and as a precursor for the creation of organoelement aerogels, which are in high demand in modern materials science. 56,57 At the same time, during the hydrosilylation reactions, the migration of the allyl double bond in carborane 1 in some cases was found to form 9-propenyl-m-carborane 9. It was found that the double bond migration in allylcarborane 1 to the internal position with the formation of pure propenylcarborane 9 proceeded in the presence of an excess of Karstedt's catalyst compared to the amount of catalyst utilized in the hydrosilylation reaction (carborane : catalyst ratio was 5.4 : 9.13 Â It is worth noting that for compounds containing an allyl group, a similar phenomenon has been described earlier, with the migration of a double bond to the internal position being observed in the presence of transition metal complexes, including palladium, rhodium, and iron, [58][59][60][61] but the carborane polyhedra intensified this process.…”
Section: Resultsmentioning
confidence: 99%
“…54,55 Compound 8 can be used as a binder and as a precursor for the creation of organoelement aerogels, which are in high demand in modern materials science. 56,57…”
Section: Resultsmentioning
confidence: 99%